Forecasting for Survival: Empirical Evidence on Financial Planning and Early-Stage Startup Resilience in the USA - Mashrur, Faisal Ahmed (Finance & Economics Review, 2025)
Purpose: This study examines the role of financial forecasting in enhancing the survival of early-stage startups in the United States, where failure rates are exceedingly high due to financial mismanagement and capital planning issues. Methodology: Using a dataset of 500 simulated startups designed to mirror real-world U.S. startup characteristics, we construct a proxy for forecasting behavior based on firm-level language and multi-round funding patterns. An Ordinary Least Squares (OLS) regression model is used to estimate the impact of forecasting on firm longevity, controlling for factors such as total funding raised and team size. Findings: The results indicate that startups engaging in financial forecasting survive, on average, 14 months longer than those that do not, even after controlling for key observable variables. This finding underscores the substantive effect of proactive financial planning on startup viability. Implications: The study suggests that financial forecasting should be regarded as a critical component of economic infrastructure. It recommends integrating forecasting literacy into federal entrepreneurship initiatives, incubator programs, and innovation policy frameworks. Originality: This paper represents one of the pioneering attempts to quantify the effect of financial forecasting on startup survival, utilizing a simulated dataset that captures real-world funding dynamics. It positions financial forecasting not only as a managerial tool but as a public good vital to national innovation and economic resilience.